Flow-mediated effects of virtual reality on post-pandemic resilience in Mexican university students: a cross-sectional PLS-SEM study - Guerra-Tamez, Cristobal Rodolfo (Frontiers in Education, 2025)
The present study aims to examine the association between Virtual Reality (VR) usage in higher education and Mexican university students’ emotional resilience, and to test whether flow experiences mediate this association. A cross-sectional survey of 220 students from two Mexican universities was analyzed with Partial Least Squares Structural Equation Modelling (PLS-SEM). VR usage exhibited a direct, positive association with resilience (β = 0.45, p < 0.01), an effect that was partially transmitted through flow (indirect β = 0.30, p < 0.01). Flow fully mediated the inverse associations between VR usage and anxiety, stress, and depression, and partially mediated the positive association with wellbeing. The reflective constructs demonstrated excellent reliability (α ≥ 0.94) and convergent validity (AVE ≥ 0.79). VR usage was operationalized as a formative composite derived from two complementary indicators (prior VR exposure and gaming frequency); this specification captured technological familiarity but will benefit from further refinement in forthcoming multi-institution studies. Although the data are cross-sectional, the strength and consistency of the observed pathways provide a solid foundation for longitudinal and experimental follow-ups. Overall, the findings suggest that immersive educational designs capable of reliably eliciting flow may bolster students’ capacity to navigate post-pandemic challenges.